Magnetic properties of oxygen doped samarium clusters. (31st December 2018) - Diaz-Bachs, Albert; Peters, Lars; Kirilyuk, Andrei
Abstract: Here we present the results of experimental study of magnetic properties of samarium clusters doped with a single oxygen atom. In a recent theoretical study it was observed that for pure Sm clusters a transition from fully non-magnetic to weakly magnetic occurs due to a valence change occurring at a size of eight atoms. Here we found, first, that pure Sm clusters could not be synthesized due to the strong oxidation tendency of Sm and the inability to sufficiently remove oxygen from the setup. Therefore, we studied Sm O clusters. Since the oxygen contributes to the binding, the valence transition for Sm O clusters may be expected to occur for a smaller cluster size than for pure Sm clusters. Indeed from our experiments the valence transition is indicated to occur for Sm atoms instead of . Furthermore, the observed magnetic moment as function of cluster size for Sm O clusters shows a strong dependency of the magnetic moment on the cluster size. A large total magnetic moment is observed for Sm O, Sm O, Sm O and Sm O compared to the smaller moment for Sm O to Sm O and Sm O to Sm O.